Biblioteksbladet - Språkbanken Text (University of Gothenburg, 2024)
The text is from Project Runeberg:
Biblioteksbladet, where it has partly been manually corrected by
volunteer users.

Texten är hämtad från Projekt
Runeberg: Biblioteksbladet, där den har korrekturlästs delvis av
frivilliga användare.
Biblioteksbladet
Keywords: Language Technology (Computational Linguistics); 1910s; 1920s; 1930s; journals; corpus; Natural Language Processing; Språkbehandling och datorlingvistik